ANALISIS PERBEDAAN PERSEPSI PASIEN UMUM DAN BPJS TERHADAP TINGKAT RESPONSIVENESS PELAYANAN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH TUGUREJO SEMARANG - Rizka Nur Fitriana; Chriswardani Suryawati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Responsiveness is a non-medical dimension that relates with how to treat someone and how the person's environmental conditions are treated that become one of the purposes of the Health System. The purpose of this study is to know the differences in the perceptions between general and BPJS patients towards the responsiveness level of outpatient services at Tugurejo Regional General Hospital. This study uses descriptive analytic method with cross sectional approach. The samples of this study are 160 respondents. Data analysis included univariate analysis by presenting the tables of frequency distribution and crosstab also bivariate analysis using Mann-Whitney difference test. Univariate results showed that the responsiveness level of outpatient services in terms from seven dimensions of responsiveness between general patients is more responsive than BPJS patients. Crosstab results show that female respondents and highly educated tend to assess the lack of responsiveness of the services provided. The results of bivariate analysis showed that there are significant differences between general patient responsiveness and BPJS patients responsiveness. The dimensions of responsiveness that have the differences between general and BPJS patients are the dimensions of staff friendliness, patient involvement, clarity of information and choice towards service providers. Dimensions that are considered not good are the waiting time dimension and dimensions that are both considered good are the dimensions of patient comfort and patient confidentiality. Tugurejo Regional General Hospital is expected to strive to improve health services to be more responsive services so it can fill society’s expectations and improve the patient satisfaction.